2016
DOI: 10.1111/jbg.12228
|View full text |Cite
|
Sign up to set email alerts
|

Use of high‐density SNP data to identify patterns of diversity and signatures of selection in broiler chickens

Abstract: SummaryThe development of broiler chickens over the last 70 years has been accompanied by large phenotypic changes, so that the resulting genomic signatures of selection should be detectable by current statistical techniques with sufficiently dense genetic markers. Using two approaches, this study analysed high‐density SNP data from a broiler chicken line to detect low‐diversity genomic regions characteristic of past selection. Seven regions with zero diversity were identified across the genome. Most of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
0
12
0
1
Order By: Relevance
“…By measuring dsRNA amounts and inflammatory response following digestion of dsRNA, it was established that dsRNA level in commensal Lactobacillales, which is higher than dsRNA amounts in pathogens such as Salmonella enterica serovar Typhimurium and Escherichia coli, is sufficient to induce anti-inflammatory signals via TLR3. Another study that used a high-density SNP array to investigate polymorphisms in a commercial broiler line also found that TLR3 falls within a region of positive selection [12]. This raises the interesting possibility that mutations that result in decreased TLR3 function may result in poor discrimination between commensal and pathogenic flora of the gut, that while resulting in dysbiosis, may nevertheless improve growth performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By measuring dsRNA amounts and inflammatory response following digestion of dsRNA, it was established that dsRNA level in commensal Lactobacillales, which is higher than dsRNA amounts in pathogens such as Salmonella enterica serovar Typhimurium and Escherichia coli, is sufficient to induce anti-inflammatory signals via TLR3. Another study that used a high-density SNP array to investigate polymorphisms in a commercial broiler line also found that TLR3 falls within a region of positive selection [12]. This raises the interesting possibility that mutations that result in decreased TLR3 function may result in poor discrimination between commensal and pathogenic flora of the gut, that while resulting in dysbiosis, may nevertheless improve growth performance.…”
Section: Discussionmentioning
confidence: 99%
“…Note, we refer here to transcripts rather than genes since four of the five strategies rely on normalization of SNPs and SNP effects by transcript length. 12 The first strategy (Strategy 1) defines transcripts that have accumulated the greatest number of SNPs over the past 60 years. Here we compared increases in non-synonymous SNP density between the 1957 and the 1978 lines, and the 1978 and Ross308 lines.…”
Section: Combinatorial Prioritization Strategy Identifies Candidate Gmentioning
confidence: 99%
See 1 more Smart Citation
“…Проведен анализ данных высокой плотности SNP ли-нии бройлеров для обнаружения низкого разнообразия областей генома, сформированных примерно в течение 70летней селекции (Stainton et al, 2016). Идентифициро-вано семь регионов с нулевым разнообразием (гомозигот-ных районов).…”
Section: Genomics and Gene Engineering Vavilov Journal Of Genetics Anunclassified
“…Intensive genetic selection has been the method to improve economically traits in poultry production (Alnahhas et al, 2016). Stainton et al (2017) stated that the development of broiler chickens over the last 70 years has been accompanied by large phenotypic changes In addition, poultry breeding companies have used quantitative selection practices to improve productive performance the poultry industry today (Hunton, 2006). In broiler breeding program, mainline pedigree broiler populations, categorized into male and female lines, undergo continuous genetic selection to achieve higher improvements in the major economic traits.…”
Section: Introductionmentioning
confidence: 99%